‘URF SEBAGAI METODE ISTINBATH HUKUM ISLAM (Pemikiran Hasbi Ash-Shiddieqy dengan Fiqh Indonesianya) - Emi Yasir; Shafwan Bendadeh (SYARIAH: Journal of Islamic Law, 2021)
Tengku Muhammad Hasbi Ash-Shiddieqy is one of the most influential scholars in Islamic law reform in Indonesia, he brings local traditions ('urf/'adat) as the construction of Islamic Indonesian characteristic law. According to Hasbi 'urf is the law which is alive in the community and could be fluctuated continuously and it could be a strong consideration for Islamic law implementation. Hasbi, in his scientifical oration entitled “Syariat Islam Menjawab Tantangan Zaman", which delivered on the first Anniversary ceremonial of Dies Natalis in 1961, He explained: Fiqh Indonesia, is, fiqh that established in accordance with the personality of Indonesian, suitable to Indonesian behavior and character. Currently, some of developing Fiqh in society is Fiqh Hijazi that established on the basis of 'customs and' urf prevailing in Hejaz, or fiqh Misri that established on the basis of Egyptian customs and habits, or fiqh Hindi that established on 'urf and' customs prevailing in India. Recently, Fiqh did not show its ability to effectuate ijtihad, realizing the legal rulings of fiqh in accordance with the Indonesian personality. Therefore sometimes we force Hijazi fiqh or fiqh Iraki Misri to be applied in Indonesia on the basis of imitation. To construct Indonesian personality fiqh, Hasbi set off with 'urf/ traditions living in Indonesian society, he argued that every ‘urf/ customary law can be used as the postulate provided that not conflict with the Shariah. It is not only 'urf/'customs of the Arabs, but also those who follow principles of egalitarian Islam, so that besides 'urf/'Arab customs can be used as the foundation of law istinbat. 'urf is one of the principles of usul fiqh, which makes Islamic law is always evolving and able to fulfill human needs.